Keberagaman Gender dan Kualitas Laba - Nadhifah, Nur; Bayu Tri Cahya (Haka Vyza Media, 2025)
This research examined and analysed the impact of gender diversity in the boards of directors, independent commissioners, and audit committees on the quality of a company’s earnings. The quality of earnings is a crucial marker in evaluating a company’s financial performance, which is reported to interested parties. Gender diversity is believed to enrich perspectives in the strategic decision-making process. Meanwhile, the supervisory function of independent commissioners and an effective audit committee can minimise the practice of manipulating financial statements. The research method used is quantitative, with data analysis techniques in the form of multiple linear regression. The sample consists of health and technology sector companies listed on the Indonesia Stock Exchange during the 2021-2023 period, with selection criteria based on purposive sampling. The study results show that the gender diversity of the board of directors, independent commissioners, and audit committees does not affect the quality of earnings. These findings suggest that the presence of women in top management strategy positions remains limited, both in terms of numbers and their roles. The unproven influence of gender diversity in this study can be caused by the uneven proportion of genders in the top management ranks. The dominance of one gender in company leadership, both men and women, is considered not optimal in encouraging company performance, including maintaining the quality of earnings. The implications of this study emphasize the importance of strengthening the supervisory function in the corporate governance structure to improve the quality of reported financial information.